A carbon dot modified fluorescent fiber composite anti-counterfeiting film material and preparation method thereof

By chemically grafting carbon dots on the fluorescent fibers and adding antioxidants and plasticizers, the problem that fluorescent fibers are prone to fluorescent quenching at high temperatures is solved, and carbon dot modified fluorescent fiber composite with stable anti-counterfeiting function at high temperatures is achieved Anti-counterfeiting membrane material.

CN115625948BActive Publication Date: 2025-02-14WUHAN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211207845.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-02-14
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Existing fluorescent fiber anti-counterfeiting materials are prone to fluorescence quenching at high temperatures and are easily affected by external conditions, resulting in loss of anti-counterfeiting function.

Method used

Carbon dot modified fluorescent fiber composite anti-counterfeiting film material is used to chemically graft the carbon dots on the fluorescent fibers and add antioxidants and plasticizers during the processing process to ensure that the material is stable at high temperature and avoid fluorescence quenching.

Benefits of technology

It realizes the anti-counterfeiting function of fluorescent fibers at high temperatures, improves the durability and stability of the material, and is suitable for film packaging materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003873474970000161
    Figure BDA0003873474970000161
  • Figure HDA0003873474980000011
    Figure HDA0003873474980000011
  • Figure HDA0003873474980000021
    Figure HDA0003873474980000021
Patent Text Reader

Abstract

The present invention discloses a carbon point modified fluorescent fiber composite anti-counterfeiting film material, which is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon point modified fluorescent fiber; 50 to 99 parts of thermoplastic film-forming resin; 1 to 20 parts of compatibilizer; 1 to 5 parts of plasticizer. The present invention adopts a bottom-up method to prepare carbon points, and obtains carbon points by carbonizing small molecules or polymers under certain reaction conditions, and uses a wide range of raw materials; and uses a hydrothermal synthesis method to dissolve small molecule precursors in water or other solvents, which has the advantages of simple operation, low cost, high production efficiency, high product fluorescence quantum yield (QY), energy saving and environmental protection, and can meet the needs of industrial large-scale production; carbon points are used as fluorescent substances, and are combined with fiber substrates by chemical grafting, which avoids the aggregation state fluorescence quenching of carbon points.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-counterfeiting film materials, and in particular to a carbon dot-modified fluorescent fiber composite anti-counterfeiting film material and a preparation method thereof. Background Art

[0002] The existence of counterfeit and inferior goods has a serious impact on society, forcing people to consider the prevention and identification of counterfeit and inferior goods, that is, anti-counterfeiting and identification. The purpose of anti-counterfeiting technology research is to provide methods for anti-counterfeiting and identification of counterfeit and inferior goods from a technical perspective, so that counterfeit and inferior goods cannot be released or can be quickly eliminated from the circulation field. The anti-counterfeiting information based on traditional anti-counterfeiting materials is easily separated from the film substrate, resulting in the loss of its anti-counterfeiting function.

[0003] Fluorescent fiber anti-counterfeiting technology is one of the core technologies of anti-counterfeiting materials. Fluorescent fiber has many characteristics such as controllable excitation spectrum, special nanomorphology and colorless and transparent appearance. Therefore, it shows excellent adaptability in anti-counterfeiting technology. It is an important anti-counterfeiting information marker. It can be used as an anti-counterfeiting substrate and is widely used in packaging anti-counterfeiting, military camouflage, road and high-altitude protective clothing, daily necessities, special photosensitive materials and information storage materials. Many fields. Fluorescent fibers developed by traditional technology will undergo fluorescence quenching when heated, so they cannot be applied to film packaging materials through the thermoplastic processing process, and are easily affected by external conditions, such as light, solvents, acids and alkalis, which cause them to lose their fluorescent properties and no longer have the function of fluorescent anti-counterfeiting. Therefore, the development of a new dual-wavelength fluorescent anti-counterfeiting fiber that is resistant to high temperatures, durable and highly stable has great application prospects and social benefits. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a carbon dot modified fluorescent fiber composite anti-counterfeiting film material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A carbon dot modified fluorescent fiber composite anti-counterfeiting film material is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon dot modified fluorescent fiber; 50 to 99 parts of thermoplastic film-forming resin; 1 to 20 parts of compatibilizer; and 1 to 5 parts of plasticizer.

[0007] Preferably, the carbon dot size of the carbon dot-modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon dot-modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon dot-modified fluorescent fiber is 2 to 6 mm.

[0008] A method for preparing a carbon dot-modified fluorescent fiber composite anti-counterfeiting film material comprises the following steps:

[0009] S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid;

[0010] S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained;

[0011] S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at a temperature of about 5°C for use;

[0012] S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot solution are placed in an 80 mL autoclave lined with polytetrafluoroethylene, and then 0-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the autoclave is sealed and reacted in an oven at 60-200° C. for 4-10 hours. After the autoclave is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60° C. for 12-48 hours to finally obtain a fluorescent fiber with a length of 2-6 mm.

[0013] S5, adding the carbon dot-modified fluorescent fiber, thermoplastic film-forming resin, plasticizer, compatibilizer and antioxidant into the feeding zone of the high-speed mixer through a liquid metering pump quantitative feeding device according to the mass components, and fully mixing them in the high-speed mixer;

[0014] S6, using a twin-screw extruder to extrude and granulate the blend, and setting the temperature of each heating section to: 150°C to 200°C for the first section, 160°C to 220°C for the second section, 180°C to 240°C for the third section, 200°C to 240°C for the fourth section, and 180°C to 230°C for the fifth section;

[0015] S7, vacuum drying the granulated carbon point modified fluorescent fiber composite material at 50° C. to 80° C. for 12 h to 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0016] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0017] Preferably, the molecular cutoff of the dialysis membrane in step S2 is MWCO:1000.

[0018] Preferably, the carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol.

[0019] Preferably, the heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine.

[0020] Preferably, the fiber base material in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, nylon, polyester, acrylic fiber, spandex, vinylon, polypropylene fiber, chloroprene fiber, and soybean fiber.

[0021] Preferably, the antioxidant in step S5 is one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant DNP, antioxidant DLTP, antioxidant TNP, antioxidant MB, and antioxidant 264, or a mixture of several of them.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a bottom-up method to prepare carbon dots. Carbon dots are obtained by carbonizing small molecules or polymers under certain reaction conditions, and the raw materials used are widely available. The small molecule precursors are dissolved in water or other solvents by a hydrothermal synthesis method. The method has the advantages of simple operation, low cost, high production efficiency, high product fluorescence quantum yield (QY), energy saving and environmental protection, and can meet the needs of industrial large-scale production.

[0024] 2. The present invention uses carbon dots as fluorescent substances, which are combined with fiber substrates by chemical grafting to avoid fluorescence quenching of carbon dots in aggregated state. At the same time, antioxidants are added during the processing to avoid fluorescence quenching caused by oxidation of the fluorescent substances by dissolved oxygen during the processing. Plasticizers are added to reduce the processing temperature to avoid thermal quenching of the fluorescent substances caused by excessively high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the Fourier transform infrared spectrum;

[0026] Figure 2 is the average particle size distribution diagram of carbon dot nanoparticles;

[0027] Figure 3 This is the excitation spectrum of the carbon dot modified fluorescent fiber composite anti-counterfeiting film;

[0028] Figure 4 This is the scanning electron microscopy image of carbon dot-modified fluorescent fiber;

[0029] Figure 5 This is a projection electron micrograph of carbon dot-modified fluorescent fiber. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] A carbon dot modified fluorescent fiber composite anti-counterfeiting film material is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon dot modified fluorescent fiber; 50 to 99 parts of thermoplastic film-forming resin; 1 to 20 parts of compatibilizer; and 1 to 5 parts of plasticizer.

[0032] The carbon dot size of the carbon dot-modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon dot-modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon dot-modified fluorescent fiber is 2 to 6 mm.

[0033] A method for preparing a carbon dot-modified fluorescent fiber composite anti-counterfeiting film material comprises the following steps:

[0034] S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid;

[0035] S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained;

[0036] S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at a temperature of about 5°C for use;

[0037] S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot solution are placed in an 80 mL autoclave lined with polytetrafluoroethylene, and then 0-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the autoclave is sealed and reacted in an oven at 60-200° C. for 4-10 hours. After the autoclave is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60° C. for 12-48 hours to finally obtain a fluorescent fiber with a length of 2-6 mm.

[0038] S5, adding the carbon dot-modified fluorescent fiber, thermoplastic film-forming resin, plasticizer, compatibilizer and antioxidant into the feeding zone of the high-speed mixer through a liquid metering pump quantitative feeding device according to the mass components, and fully mixing them in the high-speed mixer;

[0039] S6, using a twin-screw extruder to extrude and granulate the blend, and setting the temperature of each heating section to: 150°C to 200°C for the first section, 160°C to 220°C for the second section, 180°C to 240°C for the third section, 200°C to 240°C for the fourth section, and 180°C to 230°C for the fifth section;

[0040] S7, vacuum drying the granulated carbon point modified fluorescent fiber composite material at 50° C. to 80° C. for 12 h to 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0041] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0042] The molecular cutoff of the dialysis membrane in step S2 is MWCO:1000.

[0043] The carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol.

[0044] The heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine.

[0045] The fiber substrate in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, nylon, polyester, acrylic fiber, spandex, vinylon, polypropylene fiber, chloroprene fiber, and soybean fiber.

[0046] The antioxidant in step S5 is one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant DNP, antioxidant DLTP, antioxidant TNP, antioxidant MB, and antioxidant 264, or a mixture of several of them.

[0047] Example 1

[0048] S1. Mix 5g of citric acid and 3g of ethylenediamine in deionized water to form a uniform solution, then transfer the solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave tightly and place it in an oven, set the reaction temperature to 180°C, and the reaction time to 8h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0049] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 10000rpm for 30min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12h, and then filtered with a 2um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 4h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.7nm was obtained;

[0050] S3, placing a polyester fiber with a length of 10 mm in anhydrous ethanol for ultrasonic treatment for 2 hours, then rinsing with deionized water, immersing the rinsed fiber substrate in a 2 mol / L 2-methyl-1,5-diaminopentane solution, reacting in a 50°C water bath for 20 hours for amino modification, taking out the amino-modified fiber, rinsing it with deionized water, and placing it in 0.5 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), 0.1 mol / L N-hydroxysuccinimide (NHS) and 1 mol / L MES buffer for cross-linking reaction, shaking it in a shaker at 25°C for 2 hours, then rinsing it with deionized water, and then placing it in a refrigerator at a temperature of about 5°C for standby use;

[0051] S4, put 3g of surface-modified polyester fiber and 30mL of carbon dot powder into an 80mL high-pressure reactor with a polytetrafluoroethylene liner, and then add 10mL of deionized water to ensure that the fiber is immersed in the liquid. Then, seal the high-pressure reactor and react in an oven at 180°C for 8h. After the reactor is cooled, take out the sample, filter it, and wash it with deionized water for 8 times until the filtrate has no fluorescent reaction. Dry the obtained fiber in a vacuum drying oven at 50°C for 12h to finally obtain a fluorescent fiber with a length of 7mm.

[0052] S5. Mix the components and their mass ratios: carbon dot modified fluorescent fiber: 0.5 parts; polyethylene: 83 parts; PE-g-MAH: 15 parts; glycerol: 0.5 parts; antioxidant CA: 0.6 parts; antioxidant DLTP: 0.4 parts;

[0053] The liquid is added to the feeding area of ​​the high-speed mixer through a liquid metering pump quantitative feeding device and fully mixed in the high-speed mixer;

[0054] S6, extruding and granulating the blend by a twin-screw extruder, and setting the temperature of each heating section to: 160° C. for the first section, 170° C. for the second section, 180° C. for the third section, 200° C. for the fourth section, and 200° C. for the fifth section;

[0055] S7, vacuum drying the granulated carbon dot-modified fluorescent fiber composite material at 50° C. for 12 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0056] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0057] Example 2

[0058] S1. Mix 4 g of citric acid and 2 g of polyethyleneimine in 30 mL of deionized water to form a uniform solution, then transfer the solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave tightly and place it in an oven, set the reaction temperature to 160°C, and react for 10 h. After the reaction is complete, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0059] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 8000 rpm for 30 min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12 h, and then filtered with a 2 um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24 h using a dialysis membrane (molecular cutoff of MWCO: 1000), and the ultrapure water was replaced every 4 h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 6.3 nm was obtained;

[0060] S3, placing a polyester fiber with a length of 20 mm in anhydrous ethanol for 3 hours of ultrasonic treatment, then rinsing with deionized water, immersing the rinsed fiber substrate in a 1.5 mol / L 2-methyl-1,5-diaminopentane solution, reacting in a 60°C water bath for 15 hours for amino modification, taking out the amino-modified fiber, rinsing it with deionized water, and placing it in 20 mL of 15% (volume fraction) glutaraldehyde solution, shaking it in a shaker at 30°C for 4 hours, then rinsing it with deionized water, and then placing it in a refrigerator at a temperature of about 5°C for standby use;

[0061] S4, placing the surface-modified polyester fiber and the carbon dot powder into a high-pressure reactor, and then adding 30 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, the high-pressure reactor is sealed and reacted in an oven at 160°C for 10 hours. After cooling, the fiber is filtered and washed until it is neutral. The obtained fiber is dried at 80°C for 12 hours to finally obtain a fluorescent fiber with a length of 8 mm.

[0062] S5. Mix the components and their mass ratios: carbon dot modified fluorescent fiber: 1.6 parts; polypropylene: 76 parts; PP-g-MAH: 20 parts; polyvinyl alcohol: 1.4 parts; antioxidant 1010: 1 part.

[0063] The liquid is added to the feeding area of ​​the high-speed mixer through a liquid metering pump quantitative feeding device and fully mixed in the high-speed mixer;

[0064] S6, using a twin-screw extruder to extrude and granulate the blend, and setting the temperature of each heating section to: 160° C. for the first section, 175° C. for the second section, 175° C. for the third section, 180° C. for the fourth section, and 180° C. for the fifth section;

[0065] S7, vacuum drying the granulated carbon dot-modified fluorescent fiber composite material at 80° C. for 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0066] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0067] Example 3

[0068] S1. Mix 5 g of acrylic acid and 3 g of ethylenediamine in 30 mL of deionized water to form a uniform solution, then transfer the solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave tightly and place it in an oven, set the reaction temperature to 180°C, and react for 10 h. After the reaction is complete, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0069] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 10000 rpm for 25 min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12 h, and then filtered with a 1 um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24 h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 4 h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.8 nm was obtained;

[0070] S3, placing a 20 mm long polyacrylonitrile fiber in anhydrous ethanol for ultrasonic treatment for 1 hour, then rinsing with deionized water, immersing the rinsed fiber substrate in a 1.5 mol / L 2-methyl-1,5-diaminopentane solution, reacting in a 60°C water bath for 15 hours for amino modification, taking out the amino-modified fiber, rinsing it with deionized water, and placing it in 20 mL of 25% (volume fraction) glutaraldehyde solution, shaking it in a shaker at 25°C for 5 hours, then rinsing it with deionized water, and then placing it in a refrigerator at a temperature of about 5°C for standby use;

[0071] S4, placing the surface-modified polyester fiber and the carbon dot powder into a high-pressure reactor, and then adding 40 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, the high-pressure reactor is sealed and reacted in an oven at 175°C for 8 hours. After cooling, the fiber is filtered and washed until it is neutral. The obtained fiber is dried at 60°C for 12 hours to finally obtain a fluorescent fiber with a length of 10 mm.

[0072] S5. Mix the components and their mass ratios: carbon dot modified fluorescent fiber: 1.2 parts; polypropylene: 78.6 parts; PP-g-ST: 18 parts; glycerol: 0.6 parts; sorbitol: 0.8 parts; antioxidant 1076: 0.8 parts;

[0073] The liquid is added to the feeding area of ​​the high-speed mixer through a liquid metering pump quantitative feeding device and fully mixed in the high-speed mixer;

[0074] S6, extruding and granulating the blend by a twin-screw extruder, and setting the temperature of each heating section to: 170° C. for the first section, 175° C. for the second section, 180° C. for the third section, 180° C. for the fourth section, and 185° C. for the fifth section;

[0075] S7, vacuum drying the granulated carbon dot-modified fluorescent fiber composite material at 80° C. for 12 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0076] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0077] Example 4

[0078] S1. Mix 4 g starch and 3 g urea in 30 mL deionized water to form a uniform solution, then transfer the solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave tightly and place it in an oven, set the reaction temperature to 200 ° C, and the reaction time is 10 h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0079] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 9000rpm for 30min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12h, and then filtered with a 2um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 4h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 7.8nm was obtained;

[0080] S3, placing a nylon fiber with a length of 20 mm in anhydrous ethanol for ultrasonic treatment for 2 hours, then rinsing with deionized water, immersing the rinsed fiber substrate in a 2-methyl-1,5-diaminopentane solution with a concentration of 3 mol / L, reacting in a water bath at 80°C for 20 hours for amino modification, taking out the amino-modified fiber, rinsing it with deionized water, and placing it in 20 mL of 25% (volume fraction) glutaraldehyde solution, shaking it in a shaker at 25°C for reaction for 5 hours, then rinsing it with deionized water, and then placing it in a refrigerator at a temperature of about 5°C for standby use;

[0081] S4, placing the surface-modified nylon fiber and carbon dot powder into a high-pressure reactor, adding 30 mL of deionized water to ensure that the fiber is immersed in the liquid, then sealing the high-pressure reactor and reacting it in an oven at 190°C for 10 hours, cooling, filtering, washing until neutral, and drying the obtained fiber at 70°C for 12 hours to finally obtain a fluorescent fiber with a length of 12 mm;

[0082] S5. Mix the components and their mass ratios: carbon dot modified fluorescent fiber: 1.2 parts; polyethylene terephthalate: 81 parts; POE-g-MAH: 15 parts; polyvinyl alcohol: 0.8 parts; glycerol: 0.9 parts; antioxidant CA: 0.6 parts; antioxidant 164: 0.5 parts;

[0083] The liquid is added to the feeding area of ​​the high-speed mixer through a liquid metering pump quantitative feeding device and fully mixed in the high-speed mixer;

[0084] S6, extruding and granulating the blend by a twin-screw extruder, and setting the temperature of each heating section to: 165° C. for the first section, 170° C. for the second section, 180° C. for the third section, 185° C. for the fourth section, and 185° C. for the fifth section;

[0085] S7, vacuum drying the granulated carbon dot-modified fluorescent fiber composite material at 80° C. for 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0086] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0087] Example 5

[0088] S1. Mix 5 g of glucose and 2 g of polyethyleneimine in 35 mL of deionized water to form a uniform solution, then transfer the solution to a polytetrafluoroethylene-lined autoclave, seal the autoclave tightly and place it in an oven, set the reaction temperature to 180 ° C, and the reaction time to 10 h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0089] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 10000 rpm for 25 min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 24 h, and then filtered with a 1 um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24 h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 4 h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 8.6 nm was obtained;

[0090] S3, placing 8 mm long aramid fiber in anhydrous ethanol for 4 h of ultrasonic treatment, then rinsing with deionized water, immersing the rinsed fiber substrate in a 3 mol / L 2-methyl-1,5-diaminopentane solution, reacting in a water bath at 80°C for 25 h for amino modification, taking out the amino-modified fiber, rinsing it with deionized water, and placing it in 20 mL of 30% (volume fraction) glutaraldehyde solution, shaking it in a shaker at 25°C for 5 h, then rinsing it with deionized water, and then placing it in a refrigerator at a temperature of about 5°C for standby use;

[0091] S4, placing the surface-modified polyester fiber and the carbon dot powder into a high-pressure reactor, and then adding 30 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, the high-pressure reactor is sealed and reacted in an oven at 175°C for 10 hours. After cooling, the reaction is performed by suction filtration and washed until it is neutral. The obtained fiber is dried at 80°C for 12 hours to finally obtain a fluorescent fiber with a length of 6 mm.

[0092] S5. Mix the components and their mass ratios: carbon dot modified fluorescent fiber: 0.8 parts; polyethylene: 78.6 parts; PE-g-ST: 18 parts; polyvinyl alcohol: 0.4 parts; polyethylene glycol: 1.2 parts; antioxidant CA: 1 part;

[0093] The liquid is added to the feeding area of ​​the high-speed mixer through a liquid metering pump quantitative feeding device and fully mixed in the high-speed mixer;

[0094] S6, extruding and granulating the blend by a twin-screw extruder, and setting the temperature of each heating section to: 170° C. for the first section, 175° C. for the second section, 175° C. for the third section, 180° C. for the fourth section, and 185° C. for the fifth section;

[0095] S7, vacuum drying the granulated carbon dot-modified fluorescent fiber composite material at 80° C. for 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers;

[0096] S8. Add the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compound them with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product.

[0097] The reaction equation involved in the present invention is:

[0098]

[0099] Advantages of the present invention:

[0100] 1) Anti-counterfeiting information markers are difficult to separate. The fluorescent material used in the chemical attachment method is used to obtain nano-organic fluorescent fibers. The migration rate of the fluorescent material used is extremely low, and it is impossible to use existing analytical instruments for sampling, separation and component analysis. It has extremely high anti-counterfeiting effectiveness in the field of thin film materials, further enhancing technical security and anti-counterfeiting reliability. Its anti-counterfeiting effectiveness is unmatched by traditional anti-counterfeiting technology, and the market potential is huge.

[0101] 2) Successfully combine fluorescent fibers and film substrates into a continuous phase structure through thermoplastic processing. It is difficult to separate anti-counterfeiting information markers such as nanostructures and fluorescent substances. It is suitable for full-area anti-counterfeiting of plastic films, paper-plastic composite films and other film materials, improving the overall technical security and effectively avoiding illegal prevention and theft of anti-counterfeiting information.

[0102] 3) Avoid fluorescence quenching caused by thermal processing. The single fiber dispersion of nano fluorescent fibers in the resin matrix is ​​achieved by treating with surfactants and antioxidants during thermal processing, which not only avoids the fluorescence quenching caused by thermal processing, but also effectively improves the compatibility between its components, solves the core problem of compatibility between anti-counterfeiting substrates and film materials, and realizes the design and molding of fluorescent fiber anti-counterfeiting films.

[0103] 4) In addition to the characteristics of traditional fluorescent anti-counterfeiting materials such as good concealment, easy identification, and stable performance, the carbon dot modified fluorescent fiber composite anti-counterfeiting film also has a special anti-counterfeiting function. Without affecting the basic properties of the film, it also has fluorescent characteristics and fiber structure, and has both first-line and second-line anti-counterfeiting functions.

[0104] Reference Figure 1 , Figure 1The infrared spectrum of the carbon dot nanoparticles of the present invention is analyzed by Fourier infrared spectrometer for CDs, PANF and PANF-g-CDs, and it is found that there are obvious characteristic peaks at 1643cm-1, 1560cm-1, 1470cm-1 and 1389cm-1 in the infrared spectrum of CDs. According to relevant data, the peak at 1643cm-1 belongs to the C=O stretching vibration peak, the characteristic peak at 1560cm-1 belongs to the NH bending vibration peak, the peak at 1470cm-1 belongs to the C=H stretching vibration peak, and the peak at 1389cm-1 belongs to the CN stretching vibration peak. There are obvious characteristic peaks at 2956cm-1 and 1731cm-1 in the infrared spectrum of PANF. According to relevant data, the peak at 2956cm-1 belongs to the -C≡N stretching vibration peak, and the peak at 1731cm-1 belongs to the CH bending vibration peak. Compared with PAN, PAN-g-CDs showed two new characteristic peaks at 1479 cm-1 and 1271 cm-1, corresponding to the stretching vibrations of NH and NC on the secondary amide, respectively, which indicated that CDs were successfully grafted on PAN.

[0105] Reference Figure 2 , Figure 2 The average particle size distribution of the carbon dot nanoparticles of the present invention is shown in the particle size distribution test results measured by a dynamic light scattering instrument. The carbon dot particles are evenly distributed, indicating that the carbon dots have good dispersibility in the aqueous solution and no agglomeration occurs. The particle size distribution of the carbon dots is narrow, the particle size is uniform, and the average particle size is 5.5nm.

[0106] Reference Figure 3 , Figure 3 This is the excitation spectrum of the carbon dot-modified fluorescent fiber composite anti-counterfeiting film of the present invention. Under ultraviolet excitation of 340nm, the emission peak was observed to be located at 410nm, which indicates that the composite anti-counterfeiting film can emit blue-violet fluorescence under ultraviolet light of 340nm.

[0107] Reference Figure 4 , Figure 4 This is a scanning electron microscope image of the carbon dot-modified fluorescent fiber of the present invention. It can be seen from the image that the modified fiber can still maintain a complete fiber structure and has a relatively smooth surface. The average fiber diameter calculated using ImageJ software is 24.68 μm.

[0108] Reference Figure 5 , Figure 5 This is a transmission electron microscope image of the carbon dot-modified fluorescent fiber of the present invention. The carbon dots grafted on the fiber are spherical. The average particle size of the carbon dots grafted on the fiber calculated by ImageJ software is 6.39 nm.

[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A carbon dot modified fluorescent fiber composite anti-counterfeiting film material, characterized in that: The invention is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon point modified fluorescent fiber; 50 to 99 parts of thermoplastic film-forming resin; 1 to 20 parts of compatibilizer; 1 to 5 parts of plasticizer, wherein the carbon point size of the carbon point modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon point modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon point modified fluorescent fiber is 2 to 6 mm; The method for preparing the carbon dot-modified fluorescent fiber composite anti-counterfeiting film material comprises the following steps: S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid; S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained; S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at 5°C for standby use; S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot aqueous solution are placed in an 80 mL autoclave lined with polytetrafluoroethylene, and 10-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the autoclave is sealed and reacted in an oven at 60-200° C. for 4-10 hours. After the autoclave is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60° C. for 12-48 hours to finally obtain a fluorescent fiber with a length of 2-6 mm. S5, adding the carbon dot-modified fluorescent fiber, thermoplastic film-forming resin, plasticizer, compatibilizer and antioxidant into the feeding zone of the high-speed mixer through a liquid metering pump quantitative feeding device according to the mass components, and fully mixing them in the high-speed mixer; S6, using a twin-screw extruder to extrude and granulate the blend, and setting the temperature of each heating section to: 150°C to 200°C for the first section, 160°C to 220°C for the second section, 180°C to 240°C for the third section, 200°C to 240°C for the fourth section, and 180°C to 230°C for the fifth section; S7, vacuum drying the granulated carbon point modified fluorescent fiber composite material at 50° C. to 80° C. for 12 h to 24 h to make the moisture content ≤ 0.1 wt %, to obtain resin pellets carrying fluorescent fibers; S8, adding the resin pellets carrying the fluorescent fibers into the surface layer barrel through a multi-layer co-extrusion film blowing machine, and compounding with the multi-layer film through a blow molding method to obtain a carbon point modified fluorescent fiber composite anti-counterfeiting film product; The molecular cutoff of the dialysis membrane in step S2 is MWCO: 1000; The carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol; The heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine; The fiber substrate in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, nylon, polyester, acrylic fiber, spandex, vinylon, polypropylene fiber, chloroprene fiber, and soybean fiber; The antioxidant in step S5 is one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant DNP, antioxidant DLTP, antioxidant TNP, antioxidant MB, and antioxidant 264, or a mixture of several of them.

Citation Information

Patent Citations

  • Nano fluorescent fiber anti-counterfeiting film and preparation method thereof

    CN105949622A

  • Preparation method for fluorescent nano-cellulose compound aerogel

    CN109180993A